A revision of the genus Anthoceros (Anthocerotaceae, Anthocerotophyta) in China - Peng, Tao; Zhu, Rui-Liang (Phytotaxa, 2013)
The genus Anthoceros (Anthocerotaceae, Anthocerotopsida) in China is reviewed. Five species and one variety are recognized. Anthoceros alpinus, A. bharadwajii, and A. subtilis, are reported new to China. Aspiromitus areolatus and Anthoceros esquirolii are proposed as new synonyms of Folioceros fuciformis and Phaeoceros carolinianus, respectively. A key to the species of Anthoceros in China is provided.